Primary cutaneous lymphomas. Diagnostic and therapeutic guidelines of the Polish Dermatological Society (PTD) and Polish Lymphoma Research Group (PLRG) - Sokołowska-Wojdyło, Małgorzata; Olszewska, Berenika; Chmielowska, Ewa; Robak, Ewa; Prochorec-Sobieszek, Monika; Kamińska-Winciorek, Grażyna; Maj, Joanna; Kowalczyk, Anna; Reich, Adam; Lesiak, Aleksandra; Narbutt, Joanna; Szepietowski, Jacek; et al. (Dermatology Review/Przegląd Dermatologiczny, 2023)
Primary cutaneous lymphomas are a heterogeneous group of rare lymphoproliferative diseases that are initially limited to the skin but potentially also involve the lymph nodes, blood, and occasionally visceral organs. They develop from mature T cells, B cells, and NK cells. The classification includes a wide range of pathologies, each characterized by distinct clinical symptoms and variations in disease course. Cutaneous lymphomas are typically chronic in nature, and a complete cure is rarely achievable. Since primary cutaneous lymphomas are uncommon and present in many variants, they pose diagnostic and therapeutic challenges that require multidisciplinary collaboration between dermatologists, pathologists, hematologists, and oncologists. We present revised guidelines for the diagnosis and treatment of primary cutaneous lymphomas, with the goal of simplifying the diagnostic and therapeutic procedure in routine clinical practice. The guidelines cover the clinical, histopathological, and dermoscopic characteristics of skin lesions, along with recommendations for the diagnostic and therapeutic management of primary cutaneous lymphomas. When selecting the most suitable therapeutic approach for individual patients diagnosed with primary cutaneous lymphoma, the main factor to consider should be the clinical stage of the disease. However, other factors, such as the patient’s age, overall health, and medical history, should also be taken into account. The choice of therapy should be guided by finding optimal efficacy and safety. The guidelines also include globally recognized therapeutic approaches that are currently not accessible in Poland. The recommendations rely on the existing Polish and global guidelines, and the knowledge and experience of experts.